A comparative study of the nutritional, education and immunisation profile of children visiting tertiary care centre-is there a gender preference or no? - Ramagopal, Ganavi; Umadevi, Lala (International Journal Of Community Medicine And Public Health, 2016)
Background: Girls in the country are found to be at a higher risk of malnutrition and growth retardation. Status report of ‘Save the Children’ highlighted that India is having largest gender survival gap in the World. Aim of the study was to study the nutrition, education and immunization profile of children visiting tertiary care centre, to know gender preference is there or no. Methods: A descriptive study was conducted in, CHRI for a period of 6 months, where parents of all Children aged 5 -15 years were subjected to questionnaire regarding the education, immunisation and socio economic status in a predesigned proforma and their nutritional status was assessed using the anthropometric measurements and clinical examination. Results: Out of 1020 children the proportion of boys (49%) and girls (51%). The proportion of fully immunized children in females (63.1%) compared to males (70.4%). The proportion of male children going to government and private schools was 12.4% and 87.6% respectively and 10.8% and 89.2% respectively in females. The proportion of underweight children in males (5.2%), compared to females (4.2%). Conclusions: There was no there was no gender preference with regard nutritional, immunisation or educational status of the children.